Teaching responsible creativity: a path to ethical innovation - Kevin Rebecchi; Lubart Todd; Hélène Hagège (Springer, 2024)
Abstract Education today is evolving to foster essential psychosocial skills like creativity, critical thinking, and responsibility, equipping students for 21st-century challenges. However, it is crucial to examine the motivations driving these changes and their alignment with broader societal goals beyond merely economic interests. This article explores the ethical dimensions of creativity, recognizing its potential for both positive innovation and harm. It emphasizes the neutrality of creativity and the importance of evaluating the intentions and consequences behind creative acts, not just their outcomes. We introduce and define the concept of ''responsible creativity,'' characterized by the ability to generate original ideas, behaviors, or objects while considering the moral and legal repercussions of one's actions, both in the present and future. This concept is anchored in the ethics of conviction and responsibility, promoting a fundamental commitment to avoid harm and enhance well-being. Our model of responsible creativity incorporates qualities such as benevolence, flexibility, positivity, reliability, accountability, reflexivity, and wisdom. We advocate for nurturing this type of creativity in educational settings through innovative approaches such as board and video games, philosophy workshops, wisdom education, and mindfulness meditation. These pedagogical methods aim to cultivate future leaders who are ethically aware and capable of using their creativity to positively impact society and the environment. By navigating the interplay of creativity and ethics, this article provides valuable insights and practical guidance for educators and policymakers striving to create a more ethically conscious and innovative educational landscape.